2018
DOI: 10.1002/lt.25313
|View full text |Cite
|
Sign up to set email alerts
|

The Reactive Oxygen Species–Mitophagy Signaling Pathway Regulates Liver Endothelial Cell Survival During Ischemia/Reperfusion Injury

Abstract: Ischemia/reperfusion injury (IRI) is the main cause of complications following liver transplantation. Reactive oxygen species (ROS) were thought to be the main regulators of IRI. However, recent studies demonstrate that ROS activate the cytoprotective mechanism of autophagy promoting cell survival. Liver IRI initially damages the liver endothelial cells (LEC), but whether ROS-autophagy promotes cell survival in LEC during IRI is not known. Primary human LEC were isolated from human liver tissue and exposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…FUNDC1-related mitophagy suppresses hepatocarcinogenesis via inhibition of inflammasome activation [6], [7]. During liver ischemia-reperfusion injury, ROS-modified mitophagy regulates liver endothelial cell apoptosis [8]. In NAFLD, mitophagy is significantly inhibited and defective mitophagy is deemed as the pathogenesis for the development of fatty liver disease [9].…”
Section: Introductionmentioning
confidence: 99%
“…FUNDC1-related mitophagy suppresses hepatocarcinogenesis via inhibition of inflammasome activation [6], [7]. During liver ischemia-reperfusion injury, ROS-modified mitophagy regulates liver endothelial cell apoptosis [8]. In NAFLD, mitophagy is significantly inhibited and defective mitophagy is deemed as the pathogenesis for the development of fatty liver disease [9].…”
Section: Introductionmentioning
confidence: 99%
“…When reperfusion initiates, the reestablishment of the electron transfer chain and ATP synthesis in mitochondria enables autophagy to eliminate abnormal proteins and organelles that are produced during ischemia. Enhanced hepatic mitophagy is observed at the early stages of IR in both in vivo and in vitro models, which is associated with elevated cell death and aggregated liver injury [164][165][166]. However, the autophagy capacity also becomes impaired following prolonged ischemia, which may not be sufficient to eliminate the accumulated dysfunctional mitochondria.…”
Section: Mitophagy In Liver Ischemia/reperfusion Injurymentioning
confidence: 99%
“…However, parkin deficiency elevates HIRI by decreasing mitochondrial autophagy and increasing apoptosis. Bhogal et al (2018) found that autophagy within LEC is reduced accompanying IRI increased cell death. demonstrated that impairing mitophagy contributed to aggravation of hepatic ischemia-reperfusion injury in aging mice.…”
Section: Discussionmentioning
confidence: 97%